PENGAMANAN DATA TEKS MELALUI PERPADUAN ALGORITMA BEAUFORT DAN CAESAR CIPHER - Muhammad Fadlan; Sinawati Sinawati; Aida Indriani; Evi Dianti Bintari (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2019)
The importance of maintaining data integrity and security is one of the challenges in the current digital era. One method that can be used to face this challenge is through cryptography. In cryptography there are several algorithms that can be used, one of which is the Caesar cipher algorithm. This algorithm has several disadvantages, including a limited number of characters of 26 characters. This can make the encryption results easily recognizable by other parties. This study aims to design a proposal for maintaining data security through cryptographic techniques, while addressing the problems inherent in the Caesar cipher algorithm. The combination of Caesar and Beaufort algorithm is done to overcome the existing problems. In addition, a character list of 94 characters was determined to be used in the process of encryption and decryption of text data. The result, through the integration of these two algorithms, the text cipher becomes more difficult to solve. There are two stages of the encryption process by using two different types of Keys for each stage in securing data